need help solve this equation using the elimination method 6x – 4y = 54 –9x + 2y = –69

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

need help solve this equation using the elimination method 6x – 4y = 54 –9x + 2y = –69

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Multiply the second equation by 2 nd can u plz tell me vat u get?
-18+4y=-138
yup good:) nw add this one with the first equation. terms with variable y will be elimnated. then solve for x. can u do it @yayasims21

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

i cannt can u do it
plz give it a try. if u face any difficulty when doing it plz ask. I will help u:)
ok so im suppose to add -18+4y=-138 to 6x-4y=54
ya:)
i cant do it my calculator wont let me
-18x+4y+6x-4y=-138+54 (-18x+6x)+(4y-4y)=-138+54 See if u can do it nw:)
Add the ones inside the parentheses
i cant do it i really suck at math
what is -18x+6x?
-12
-12x. what is 4y-4y?
0
yup right:) what is -138+54
-84
yup good. nw combine these results.
add them
ya.
i get -96
@ajprincess happy new year & to @yayasims21 too :)
o thanks happy new year to u 2
:)
no. remember u can add -12x with -84. nd -84 is in the right side of the equal aign. -18x+6x+4y-4y=-138+54 -12x+0=-84 -12x=-84 Divide by -12 both sides to find x. Thanx @TheViper and I wish u the same:)
:)
-12 divided by -12 is 1 and -84 is 7
remember u r dividing -12x by -12 nt -12. this leaves u with x and u r right abt getting 7:)
So ur x becomes 7. To find y plug in this value in either 6x – 4y = 54 or –9x + 2y = –69 and solve
ok wat do u mean how am i suppose to do tht
x=7. Plug this in 6x-4y=54 6(7)-4y=54 42-4y=54 1.Subtract 42 both sides. 2.Divide by -4 both sides to find y.
i cant do this im so confused
42-4y=54 1.Subtract 42 both sides. 2.Divide by -4 both sides to find y.
Plz follow the steps
i am but so im suppose to subtract 42from -9
no. let me do one step and show. 42-4y=54 Subtract 42 both sides 42-42-4y=54-42 0-4y=12 -4y=12 Nw divide by -4 both sides to find y
-3x
-4y=12 Divide by -4 both sides (-4y)/-4=12/-4 y=-3
ok i got it is there anymore we have to do
nope. evrythng is done:)
ok well can u show this all at once so i can write it down
can you @ajprincess
Extremely sorrry @yayasims21. busy right nw.
o alright illtry to put it together
hav u finished @yayasims21?
\(6x-4y=54-(1)\) \(-9x+2y=-69-(2)\) (2)*2=>\(-18x+4y=-138-(3)\) (3)+(1)=>\(-18x+4y+6x-4y=-138+54\) \(-12x=-84\) \(-12x/-12=-84/-12\) \(x=7\) Substituting this in (1)=> \(6(7)-4y=54\) \(42-4y=54\) \(-4y=54-42\) \(-4y=12\) \(-4y/-4=12/-4\) \(y=-3\)

Not the answer you are looking for?

Search for more explanations.

Ask your own question